Reprezentacje tożsamości płciowej a cele zrównoważonego rozwoju - Czerwiec, Karolina; Leżucha, Magdalena (Kultura-Społeczeństwo-Edukacja, 2024)
Identity, knowledge and personal predispositions generate the perception of gender identity and the ability to raise this issue in a social context. This includes interpersonal factors, institutional policies, and legal regulations regarding diversity and equality. Behavior deemed deviant from the norm may be pathologized by medicine, punished by the law or by people who perceive it as a threat that disrupts the normative order. The aim of the article was to characterize the assumptions of the 2030 Agenda in the context of its references to human gender identity in various dimensions. The analysis focused in particular on those of the 17 Sustainable Development Goals that concern gender equality, inequality, justice and good quality of life, health and education. It has been shown that the assumptions of the 2030 Agenda concern the creation of living conditions in which everyone will be able to develop without the feeling of fear and the threat of violence. However, there are few direct references to gender identity. It should therefore be assumed that the inclusion of gender equality goals in the document also covers aspects related to gender identity. Therefore, only joint actions of governments and non governmental organizations in the implementation of the goals and tasks of the 2030 Agenda will contribute to sustainable social development and improvement of the situation of all people in various spheres of life, including those related to the representation of gender identity.